Impactos ambientales de la empresa tabacalera la Francey S.A. del cantón Quevedo, provincia de los Ríos - Toral Vera , Yara Alejandra (2023)
Environmental impact is the alteration or modification of the environment caused directly or indirectly by the activities of a project in a given area. As a result of industrial expansion, the quality of the environment has become increasingly vulnerable, producing an accelerated decline due to the presence, development and impacts of industrial processes. For this reason, the objective of this study was to evaluate the environmental impacts generated by the activities of the company Tabacalera la Francey S.A and its impact on the environment and human health in the area of influence. To do this, the farmers' perception was known through 12 questions using the Likert scale, therefore, they were treated by Cronbach’s Alpha internal consistency analysis considering a level of reliability of the questions greater than 0,7 which were chosen and applied to the population. The results indicated that 88% of the respondents said that this company is harming natural resources and 81% of them mentioned having effects on their health. The main activities of the company that are causing a high risk of pollution are fumigation which includes the monitoring and elimination of pests, fertilization, noise and polluting emissions to air by anthropogenic sources, It should be emphasized that these impacts can be modified with alternatives for environmental improvement. The environmental management plan included feasible measures to reduce those significant negative environmental impacts, in which it is also taken as a measure to create an environmental training plan to strengthen knowledge and raise awareness of the members of the company to care for the environment and health of both them and the surrounding population. Keywords: Pollution, industry, tobacco, factors, evaluation